Operating characteristics of ground-water reservoirs occupying a trench - Glover, Robert E. (Robert Ellsworth), 1896-1984, author; Skinner, Morris M., author; Colorado State University, Department of Civil Engineering, publisher (Colorado State University. Libraries, 1961)
Sediment filled valleys of intermittent streams can be used as underground reservoirs for storage of water. Water so stored is not subject to evaporation losses and the seepage losses may be small. Recharge and operational characteristics of such reservoirs are expressed in formula form. Some comments are made in regard to the problems of water quality maintenance.
CER61MMS-75.
Presented at the annual meeting of the American Association for the Advancement of Science, December 30, 1961, Denver, Colorado.
Keywords: Artificial groundwater recharge; Groundwater